Ensuring Public Realm Through Private- private Partnership, in the Context of Rapid Urbanization (Case of CBD area Kochi). (2016) - Abhilash, R.S.; Chandy, M. Nirmal
Abstract: In the context of rapid urbanization, the lack of public space development is one of the major issues of commercial development in city cores of Kerala. The reasons of this issue are related to land division. In the present context, there are lacks of guidelines to regulate the minimum size of plot during plot subdivision. The individual plot of small size is not feasible for high density commercial development. The land reconstitutions like feasible solutions were adopted by the individual developers to develop large commercial blocks. The public spaces developed as the result of these changes are segregated, introverted and self contained entities like, space inside the commercial malls, shopping centers etc. The intent of this research is to develop the real-estate policies as an urban design tool to create an integrated public space network system in commercial core of the city, and to develop a framework of strategies for the space management models like Private-Private partnership to integrate the existing isolated hybrid spaces in to the city fabric, and to create new integrated system of public space network. A sample precinct of M.G road stretch of Kochi was taken up for demonstration after a detailed analysis of various parameters of open space such as ecology, land use, morphological pattern, and transportation infrastructure.